Management of Entrepreneurship Education in Shaping the Character of Student Independence at Hidayatul Mubtadi-Ien Islamic Boarding School - Mahdiyan Nasikhin, Moch (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
At present, pesantren face challenges from globalization and technological advances that result in the lack of availability of effective management in managing entrepreneurial programs. In addition, there is a need to provide competent educators in the field of entrepreneurship and develop mature concepts for entrepreneurship programs in pesantren. The purpose of this study is to analyze Entrepreneurship Education Management in Shaping the Character of Student Independence. This study applies a qualitative descriptive approach with a naturalistic qualitative descriptive method that emphasizes a holistic approach. The results showed that the management of entrepreneurship education at Hidayatul Mubtadi-ien Indramayu Islamic Boarding School plays an important role in shaping the character of student independence. The conclusion of this study is that the management planning of entrepreneurship education in shaping the character of student independence at the Hidayatul Mubtadi-ien Indramayu Islamic Boarding School has been carried out well. This can be seen from the preparation of planning entrepreneurial activities of students by the institution. The organization of entrepreneurial education management in shaping the character of student independence at Hidayatul Mubtadi-ien Indramayu Islamic Boarding School has also been carried out well. The institution has organized the entrepreneurial activities of students. The implementation of entrepreneurship education management in shaping the character of student independence at the Hidayatul Mubtadi-ien Indramayu Islamic Boarding School has also gone well. The institution manages Islamic boarding school cooperatives, goat farming, and fish farming with a biofloc system as student entrepreneurial activities. Supervision of entrepreneurial education management in shaping the character of student independence at Hidayatul Mubtadi-ien Indramayu Islamic Boarding School has been carried out well. The institution has conducted an assessment of the achievements of students' entrepreneurial activities